2016
DOI: 10.1017/s0954422416000093
|View full text |Cite
|
Sign up to set email alerts
|

IHD from copper deficiency: a unified theory

Abstract: The theory, in brief outline here, implicating deficiency of Cu in the aetiology and pathophysiology of IHD explains more attributes of the disease than any other theory. This theory satisfies several of Hill's criteria of a half-century ago for deducing association between an environmental feature and presence of an illness. Most important is the temporal association between the rise of IHD and the decrease in dietary Cu since the 1930s along with a parallel increase in the supplementation of pregnant women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 84 publications
3
27
0
Order By: Relevance
“…It has been suggested that iron can interfere with copper utilization (148). An experiment in rats showed that higher dietary iron can increase the dietary requirement for copper (149).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinementioning
confidence: 99%
See 3 more Smart Citations
“…It has been suggested that iron can interfere with copper utilization (148). An experiment in rats showed that higher dietary iron can increase the dietary requirement for copper (149).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinementioning
confidence: 99%
“…An experiment in rats showed that higher dietary iron can increase the dietary requirement for copper (149). Moreover, high iron consumption has been reported to interfere with copper absorption in infants and adults (148). It has been further suggested that iron overload can perturb copper utilization (295, 296).…”
Section: Intersection Of Iron and Copper Metabolism In The Intestinementioning
confidence: 99%
See 2 more Smart Citations
“…What is less widely appreciated is that the adverse effects of high fructose intakes may also increase alcohol-associated liver damage [44] . Importantly, it has been known for many years that there is an interaction through which high fructose intake can exacerbate poor copper status and together these may present as disordered lipid metabolism and increased risk of cardiovascular abnormalities [45] . Copper itself has complex metabolic interactions with other divalent cations, such as iron and zinc, which are especially evident during inflammatory states [24,25] .…”
Section: Responding To Stressmentioning
confidence: 99%